Lesbian Pregnancy: Care and Considerations - Bushe, Sierra; Romero, Iris L. (Seminars in Reproductive Medicine, 2017)
The constructs and the provision of preconception and obstetrical care have historically been based on the assumption of heterosexuality, and have often excluded lesbian women. However, due to significant strides in lesbian, gay, bisexual, transgender, and queer (LGBTQ) civil rights, more lesbian women desire to create and expand their families, and lesbian parented families are increasing. This places obstetrical care providers at the forefront of the movement to build inclusive health care environments. Therefore, it is incumbent upon those of us who work in obstetrics to understand, recognize, and respect the unique cultural considerations that pertain to lesbian women and couples seeking parenthood. This review seeks to provide culturally sensitive guidance on the specific concerns and challenges lesbians face, from preconception care to postpartum care, and briefly addresses legal issues and considerations for the nonbiologic mother. The recommendations outlined here are drawn from studies of the experiences of lesbian women with pregnancy. However, the scientific literature is very limited, and there is a clear need for additional obstetrical research focused on this patient group. As professionals committed to assuring optimal outcomes for all obstetrical patients, it is crucial that we promote the inclusion of sexual minority women in our clinical practices and research endeavors.
Keywords: lesbian; pregnancy; prenatal care; nonbiologic mother; postpartum care